Utilizing 5G Enhanced IoT Services for Improved Decision-Making in Environmental Resource Management - M. Alexander Pearl (International Telecommunications Society (ITS), 2019)
The possibilities offered by moving to a 5G infrastructure are fairly well known-decreased latency, enhanced connectivity options, and greatly improved speeds. These technological advancements will make multi-player gaming easier, decrease download time for HD media, and allow for exciting possibilities regarding development of driverless cars technologies. The possible applications for 5G technology to enhance business and leisure stretch as far as the imagination. However, this paper is not about the technical aspect of 5G technology and infrastructure, nor is this paper about how 5G opens up new economic possibilities in various markets. Instead, this paper focuses on how 5G dramatically enhances our ability to obtain data (especially in real time) which opens up significant opportunities regarding how we use data to inform and improve decision-making at all levels. I argue that the move to 5G infrastructure and technology facilitates our ability to develop and deploy new Internet of Things-based services (IoT) in critical areas-like the management of scarce environmental resources. This paper explores the possible ways in which 5G infrastructure can facilitate the creation of new IoT services that improve our responses to the two greatest interrelated environmental threats of our lifetime: climate change and water scarcity.
Keywords: 330